Laboratory X‐ray characterization of a surface acoustic wave on GaAs: the critical role of instrumental convolution. Issue 6 (11th November 2016) - Largeau, Ludovic; Camara, Ibrahima; Duquesne, Jean-Yves; Gourdon, Catherine; Rovillain, Pauline; Thevenard, Laura; Croset, Bernard
Abstract : It is demonstrated that measurement of a surface acoustic wave amplitude can be performed on a laboratory diffractometer with a careful experimental procedure and an accurate data analysis. The importance of the footprint reduction and geometrical correction factors to account for finite experimental resolution is emphasized. Abstract : Surface acoustic waves of micrometre wavelength travelling on a monocrystal give diffraction satellites around each Bragg peak in an X‐ray diffraction diagram. By using a four‐crystal monochromator, a secondary two‐crystal analyser and masks reducing the footprint to the part of the crystal containing the acoustic modulation, it is possible to observe these satellites on a GaAs (001) surface using a laboratory diffractometer. The finite extension of the satellite diffraction rods and of the crystal truncation rod perpendicular to the surface leads to geometrical correction factors when convoluted with the instrumental resolution function, which had previously been ignored. The calculation of these geometrical correction factors in the framework of the kinematic approximation allows the determination of the surface acoustic wave amplitude, and the study of its attenuation and its dependence on radiofrequency power and duty cycle. The ability to perform such determinations with a laboratory diffractometer should prove useful in optimizing surface acoustic waves, which are presently used in a broad range of condensed matter physics studies.